IN-SERVICE EFL TEACHERS’ EXPERIENCES OF CONDUCTING REFLECTIVE PRACTICE AS CONTINUING PROFESSIONAL DEVELOPMENT - Tosriadi, Tosriadi - (Universitas Negeri Makassar, 2018)
Teaching is a demanding job and it requires professional individual to perform the job. There is a need for teachers, especially language teachers to reflect on their action in order to be professional educators. To ease teachers in conducting reflective practice there are some tools that can be utilized. This qualitative case study investigated experiences of in-service EFL teachers in Indonesia in conducting reflective practice. More specifically, it discussed the tools of reflective practice employed by participating teachers in doing reflection. Four in-service EFL teachers were purposively chosen as respondents of the study. The data were acquired by spreading questionnaire, doing interview, and conducting document analysis. The results of the study revealed there were five tools of reflective practice utilezed by in-service EFL teachers in doing reflective practice, namely; teaching journal, peer observation, students’ feedback, video/audio recording, and action research. The finding of the study informed that the practice of reflective practice among in-service EFL teachers was not maximal yet. Especially on the utilization of video/audio recording and action research. Moreover, no teachers were getting involved in peer coaching activity.